Embracing the Gig Economy - Yunita, Fenny Tria (Faculty of Law, University of Jember, Indonesia, 2023)
The post-pandemic economic landscape has witnessed the emergence of a worldwide sharing economy system, commonly known as the ‘gig economy’. This system represents a significant transformation in labor and services exchange characterized by short-term jobs, freelance, or on-demand work arrangements facilitated by digital platforms. Recently, the gig economy has emerged as a highly promising employment preference due to its flexibility. However, it has also led to significant inequality issues for traditional workers. Moreover, this sharing economy system also exerts substantial impacts on the environment.